Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Let's find the value of [tex]\( w \)[/tex] in the equation:
[tex]\[ \frac{1}{(11^4)^7} = 11^w \][/tex]
We will start by simplifying the left-hand side of the equation step by step.
### Step 1: Simplify the exponent on the left-hand side
First, let's simplify [tex]\((11^4)^7\)[/tex]. We use the property of exponents that states [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (11^4)^7 = 11^{4 \cdot 7} \][/tex]
Calculate the exponent:
[tex]\[ 4 \cdot 7 = 28 \][/tex]
So, we have:
[tex]\[ (11^4)^7 = 11^{28} \][/tex]
### Step 2: Rewrite the fraction using the simplified exponent
Next, write the fraction [tex]\(\frac{1}{11^{28}}\)[/tex]:
[tex]\[ \frac{1}{11^{28}} = 11^{-28} \][/tex]
Using the property that [tex]\( \frac{1}{a^n} = a^{-n} \)[/tex], we find that:
[tex]\[ \frac{1}{11^{28}} = 11^{-28} \][/tex]
### Step 3: Equate the simplified expression to the original equation
We originally had the equation:
[tex]\[ \frac{1}{(11^4)^7} = 11^w \][/tex]
Now we know that:
[tex]\[ \frac{1}{11^{28}} = 11^{-28} \][/tex]
Substituting this into the original equation, we get:
[tex]\[ 11^{-28} = 11^w \][/tex]
### Step 4: Solve for [tex]\( w \)[/tex]
Since the bases are the same, we can equate the exponents:
[tex]\[ -28 = w \][/tex]
Thus, the value of [tex]\( w \)[/tex] is:
[tex]\[ w = -28 \][/tex]
Therefore, [tex]\( w \)[/tex] in the equation [tex]\(\frac{1}{(11^4)^7} = 11^w\)[/tex] is [tex]\(\boxed{-28}\)[/tex].
[tex]\[ \frac{1}{(11^4)^7} = 11^w \][/tex]
We will start by simplifying the left-hand side of the equation step by step.
### Step 1: Simplify the exponent on the left-hand side
First, let's simplify [tex]\((11^4)^7\)[/tex]. We use the property of exponents that states [tex]\((a^m)^n = a^{m \cdot n}\)[/tex]:
[tex]\[ (11^4)^7 = 11^{4 \cdot 7} \][/tex]
Calculate the exponent:
[tex]\[ 4 \cdot 7 = 28 \][/tex]
So, we have:
[tex]\[ (11^4)^7 = 11^{28} \][/tex]
### Step 2: Rewrite the fraction using the simplified exponent
Next, write the fraction [tex]\(\frac{1}{11^{28}}\)[/tex]:
[tex]\[ \frac{1}{11^{28}} = 11^{-28} \][/tex]
Using the property that [tex]\( \frac{1}{a^n} = a^{-n} \)[/tex], we find that:
[tex]\[ \frac{1}{11^{28}} = 11^{-28} \][/tex]
### Step 3: Equate the simplified expression to the original equation
We originally had the equation:
[tex]\[ \frac{1}{(11^4)^7} = 11^w \][/tex]
Now we know that:
[tex]\[ \frac{1}{11^{28}} = 11^{-28} \][/tex]
Substituting this into the original equation, we get:
[tex]\[ 11^{-28} = 11^w \][/tex]
### Step 4: Solve for [tex]\( w \)[/tex]
Since the bases are the same, we can equate the exponents:
[tex]\[ -28 = w \][/tex]
Thus, the value of [tex]\( w \)[/tex] is:
[tex]\[ w = -28 \][/tex]
Therefore, [tex]\( w \)[/tex] in the equation [tex]\(\frac{1}{(11^4)^7} = 11^w\)[/tex] is [tex]\(\boxed{-28}\)[/tex].
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.